The influence of biogeographic history on the functional and phylogenetic diversity of passerine birds in savannas and forests of the Brazilian Amazon. Issue 7 (3rd March 2018) - Almeida, Sara Miranda; Juen, Leandro; Sobral, Fernando Landa; Santos, Marcos Pérsio Dantas
Abstract: Passeriformes is the largest and most diverse avian order in the world and comprises the Passeri and Tyranni suborders. These suborders constitute a monophyletic group, but differ in their ecology and history of occupation of South America. We investigated the influence of biogeographic history on functional and phylogenetic diversities of Passeri and Tyranni in forest and savanna habitats in the Brazilian Amazon. We compiled species composition data for 34 Passeriformes assemblages, 12 in savannas and 22 in forests. We calculated the functional (Rao's quadratic entropy, FD Q ) and phylogenetic diversities (mean pairwise distance, MPD, and mean nearest taxon distance, MNTD), and the functional beta diversity to investigate the potential role of biogeographic history in shaping ecological traits and species lineages of both suborders. The functional diversity of Passeri was higher than for Tyranni in both habitats. The MPD for Tyranni was higher than for Passeri in forests; however, there was no difference between the suborders in savannas. In savannas, Passeri presented higher MNTD than Tyranni, while in forest areas, Tyranni assemblages showed higher MNTD than Passeri. We found a high functional turnover (~75%) between Passeri and Tyranni in both habitats. The high functional diversity of Passeri in both habitats is due to the high diversity of ecological traits exhibited by species of this group, which enables the exploitation of a wide variety of resources and foraging strategies. The higher Tyranni MPD and MNTD in forests is likely due to Tyranni being older settlers in this habitat, resulting in the emergence and persistence of more lineages. The higher Passeri MNTD in savannas can be explained by the existence of a larger number of different Passeri lineages adapted to this severe habitat. The high functional turnover between the suborders in both habitats suggests an ecological strategy to avoid niche overlap. Abstract : We investigated the functional and phylogenetic diversity of Passeriformes (Passeri and Tyranni suborders) in Amazonian, and the functional beta diversity. The patterns of functional and phylogenetic diversity were a result of both the biogeographic history of each bird group, the occurrence within each habitat type, as well as the different ecological strategies shown by the species.